Changes

Jump to: navigation, search

Lagrange mean value theorem

15 bytes added, 20:16, 20 October 2011
Proof
| 6 || There exists <math>c \in (a,b)</math> such that <math>g'(c) = 0</math>. || Fact (3) || || Steps (3), (4), (5) || <toggledisplay>Steps (3), (4), (5) together show that <math>g</math> satisfies the conditions of Rolle's theorem on the interval <math>[a,b]</math>, hence we get the conclusion of the theorem.</toggledisplay>
|-
| 7 || For the <math>c</math> obtained in step (6), <math>f'(c) = h'(c)</math> || Fact (4) || || Steps (2), (6) || <toggledisplay>From Step (2), <math>g = f - h</math>. Differentiating both sides by Fact (4), we get <math>g' = f' - h'</math> on <math>(a,b)</math>. Since <math>g'(c) = 0</math>, we obtain that <math>f'(c) = h'(c)</math>.</toggledisplay>
|-
| 8 || <math>h'(x) = \frac{f(b) - f(a)}{b - a}</math> for all <math>x</math>. In particular, <math>h'(c) = \frac{f(b) - f(a)}{b - a}</math>. || || || Step (1) || Differentiate the expression for <math>h(x)</math> from Step (1).
3,033
edits

Navigation menu